EKSPLORASI ETNOMATEMATIKA PADA KAIN TENUN MASYARAKAT DESA WOLOTOPO KECAMATAN NDONA KABUPATEN ENDE - Grasela Sare Manda; Lely Suryani; Maria Trisna Sero Wondo (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
People often don't understand that there is a mathematical element to what is done in cultural activities. Ethnomathematics is an approach that can be used to explain that social culture and mathematics have a very close relationship. One of them is the culture of the Wolotopo Village community, namely weaving which is related to mathematical elements. This study aims to find out what mathematical concepts exist in the woven fabrics of the Wolotopo Village community, Ende Regency. The research method used is qualitative with an ethnographic approach. The data collection used is observation, interviews, and documentation. The data analysis technique used is interview and observation. The results show that the mathematical concepts in the woven cloth motifs of Wolotopo Village are geometric concepts in the form of vertical lines (wound motifs), squares (rote eye motifs), rectangles (wound motifs), trapezoids (limara motifs), rhombuses (one mesa motifs), kites (wound motifs, and koko beto motifs), triangles (pea eye motifs) and circles (soke eye motifs).